Pharmacological treatment and prevention of cerebral small vessel disease: a review of potential interventions - Bath, Philip M.W.; Wardlaw, Joanna M. (SAGE, 2015)
Small vessel disease encompasses lacunar stroke, white matter hyperintensities, lacunes and microbleeds. It causes a quarter of all ischemic strokes, is the commonest cause of vascular dementia, and the cause is incompletely understood. Vascular prophylaxis, as appropriate for large artery disease and cardioembolism, includes antithrombotics, and blood pressure and lipid lowering; however, these strategies may not be effective for small vessel disease, or are already used routinely so precluding further detailed study. Further, intensive antiplatelet therapy is known to be hazardous in small vessel disease through enhanced bleeding. Whether acetylcholinesterase inhibitors, which delay the progression of Alzheimer's dementia, are relevant in small vessel disease remains unclear. Potential prophylactic and treatment strategies might be those that target brain microvascular endothelium and the blood brain barrier, microvascular function and neuroinflammation. Potential interventions include endothelin antagonists, neurotrophins, nitric oxide donors and phosphodiesterase 5 inhibitors, peroxisome proliferator-activated receptor-gamma agonists, and prostacyclin mimics and phosphodiesterase 3 inhibitors. Several drugs that have relevant properties are licensed for other disorders, offering the possibility of drug repurposing. Others are in development. Since influencing multiple targets may be most effective, using multiple agents and/or those that have multiple effects may be preferable. We focus on potential small vessel disease mechanistic targets, summarize drugs that have relevant actions, and review data available from randomized trials on their actions and on the available evidence for their use in lacunar stroke.